AKAR IKHTILAF DALAM PEMIKIRAN HUKUM ISLAM DAN CARA MENSIKAPI PERBEDAAN - M.Ag, Dr. Kholidah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
AbstraksiThis article examines the roots of ikhtilaf in Islamic legal thought and how to respond to it. With the aim of adding insight to readers so that religious narrow-mindedness is minimized. This article is library research in nature, because the data comes from the library. The data is secondary data with three types of legal material. First, primary or basic legal materials are books that discuss ikhtilfaf directly. Second, secondary or complementary legal materials in the form of explanations of primary legal materials and third, tertiary legal materials in the form of disklopedias or dictionaries. This data will then be analyzed using content analysis techniques, to then be concludedHistorically, differences of opinion in Islamic legal thought are not something new, they have been a tradition for a long time. Differences of opinion that occur among ulama are caused by many factors. The factors referred to are 1) differences in qira'ah in the Qur’an, 2) ignorance of the existence of a hadith, 3) differences in assessing a hadith, 4) show the pronunciation in the text, 5) differences in understanding and interpreting a text, 6) differences in completing ta'arud al-adillah, 7) differences in responding to cases where there is no sharih text, and 8) differences in qawa'id ushuliyahThis difference of opinion is a sunnatullah that cannot be avoided, cannot be denied, especially in Islamic law, because the text itself provides an opportunity for that. In order for these differences to become something positive, rahmatan lil'alamin, the way to do this is to study and really understand the differences of opinion themselves. Because with the knowledge and understanding he has, a person will have broad and open thinking. So that an attitude of mutual respect (empathy) emerges, and also a sporty attitude in facing differences, as exemplified by the Prophet, friend and also the imam of the sect.